Faktor–faktor yang Mempengaruhi Dividend Perusahaan Sektor Manufaktur yang Terdaftar di Bursa Efek Indonesia dan Bursa Malaysia - Fellicia Hadi Seputro; Werner Ria Murhadi; Arif Herlambang (Program MM Universitas Surabaya, 2020)
This study aims to investigate the determinants of firms dividend payout ratio, such as life cycle stage, independent non-executive director, risk, firm size, market-to-book ratio, cash to total asset, and leverage of manufacturing sector companies listed in the Indonesia Stock Exchange and Malaysia Stock Exchange in 2014-2018. This study uses the quantitative approach and multiple linear regression to analyze the data. The object of this research are 295 year observations in Indonesia Stock Exchange and 600 year observations in Malaysia Stock Exchange. The Independent variables used in this study are life cycle stage and independent non-executive directors. While the control variables are risk, firm size, market-to-book ratio, cash to total asset and leverage. The study finds that in manufacturing sector companies listed in the Indonesia Stock Exchange, life cycle stage, independent non-executive director, firm size and market-to-book ratio affect dividend payout ratio positively. On the other hand, leverage affect dividend payout ratio negatively. While risk and cash to total asset has no significant effect on dividend payout ratio. Meanwhile in manufacturing sector companies listed in the Malaysia Stock Exchange, the study finds that life cycle stage, independent non-executive director, firm size, market-to-book ratio and cash to asset affect dividend payout ratio positively. While risk and leverage affect dividend payout ratio negatively. Keywords: dividend policy, life cycle stage, independent non-executive director